SAFETY OF HYDROXYCHLOROQUINE FOR COVID-19 PROPHYLAXIS AMONG HEALTHCARE WORKERS: AN OBSERVATIONAL STUDY - KHANNA, SANGEETA; BEWAL, NITUL M; ARORA, AMIT; G V, KRISHNA PRASAD (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Indian Council of Medical Research recommended hydroxychloroquine (HCQ) for prophylaxis of COVID‐19 for healthcare workers and the Food and Drug Administration approved its use in the treatment and prophylaxis of COVID‐19 disease. Even though HCQ is adequately tolerated in usual circumstances, still questions about the harmful effects of the drug remain a cause for concern in adults treated with HCQ. The objective of this study was to evaluate the major and minor adverse effects of prophylactic HCQ for COVID-19 among healthcare workers. Methods: Our analysis was intended to analyze HCQ’s adverse drug reaction profile for COVID‐19 prophylaxis in prophylactic doses in health-care staff. This was a cross-sectional study carried out among healthcare workers taking HCQ prophylaxis for COVID‑19. The study was carried out over 08 weeks period from April to May 2020. The data were obtained regarding age, sex, comorbidities, and possible adverse effects. A pretested and validated online questionnaire was provided to the participants to assess the harmful effects that they experienced when taking HCQ. Furthermore, pre and post 8 weeks prophylaxis, individuals underwent general and systemic examination, along with ECG and blood sugar level monitoring. Results: The research group comprised 70 previously healthy and health-care staff. In 70 patients, 27 minor adverse effects were reported (18.9%). Headache was the most frequently reported symptoms followed by nausea and vomiting, itching, and skin rashes. There was no statistically relevant variation in harmful effects due to age or number of doses administered. However, none of the adverse effects was serious or debilitating. Conclusion: With adequate pre-prophylaxis evaluation, health education, and regular monitoring, HCQ prophylaxis is safe and devoid of any serious adverse effects in previously healthy individuals.